2020
DOI: 10.1002/jssc.201901330
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of thin film solid phase microextraction and data deconvolution methods for accurate characterization of organic compounds in produced water

Abstract: Funding informationThe University of Toledo The continued rise in the extraction of unconventional oil and gas across the globe poses many questions about how to manage these relatively new waste-streams.Produced water, the primary waste by-product, contains a diverse number of anthropogenic additives together with the numerous hydrocarbons extracted from the well.Due to potential environmental hazards, it is critical to characterize the chemical composition of this type of waste before proper disposal or reme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 35 publications
2
14
0
Order By: Relevance
“…Examples of more complex matrices, such as river water, likely containing a significant amount of dissolved organic matter, and produced water from the hydraulic fracking process, which is a very complex aqueous mixture of organic compounds and metals, , were also evaluated. The produced water samples were previously analyzed by Liden et al and found to contain high concentrations of common metal ions such as Na (26 000–50 000 mg L –1 ), Ca (1400–1600 mg L –1 ), Mg (100–500 mg L –1 ), and Fe (4–7 mg L –1 ), among others .…”
Section: Resultsmentioning
confidence: 99%
“…Examples of more complex matrices, such as river water, likely containing a significant amount of dissolved organic matter, and produced water from the hydraulic fracking process, which is a very complex aqueous mixture of organic compounds and metals, , were also evaluated. The produced water samples were previously analyzed by Liden et al and found to contain high concentrations of common metal ions such as Na (26 000–50 000 mg L –1 ), Ca (1400–1600 mg L –1 ), Mg (100–500 mg L –1 ), and Fe (4–7 mg L –1 ), among others .…”
Section: Resultsmentioning
confidence: 99%
“…The short equilibrium time and high sensitivity due to the usage of a relatively large extractive phase which is spread over a large surface area are unique merits of this method. 17,18 In order to enhance the efficiency of TFME methods, huge attempts have been made to fabricate and employ effective extraction phases for TFME. Among various methods for the preparation of a thin film with a large surface area, electrospinning has gained vast attention as a convenient process to synthesize porous and smooth nanofibers leading to the improvement of the adsorption efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Thin-film SPME can be used for an array of applications such as bioanalysis, food, and environmental monitoring. For example, SPME is often used to analyze air quality or water quality in environmental studies, the presence of specific nutrients or toxins in food, and the existence of specific compounds in pharmaceuticals—or of pharmaceuticals in other matrices [ 27 , 28 , 29 , 30 , 31 ]. Frequently, TF-SPME methods can replace existing methods for analyzing these compounds; as such it is necessary to compare the existing methods with the newly developed TF-SPME methods to ascertain that the new methods are indeed more sustainable—and that the analysis results are of comparable or superior quality [ 27 , 32 ].…”
Section: Introductionmentioning
confidence: 99%